Meningkatkan Kemandirian Anak Usia 5-6 Tahun Melalui Metode Pembiasaan Pada Anak Usia Dini Di Kelompok B Tk It Khadijah Al Kubro - Rahma Yumita; Vitri Angraini Hardi; Lusi Marleni (Jurnal Pendidikan Tuntas, 2024)
This research is motivated by the ability of independence in children at Khadijah Al-Kubro Kindergarten has not developed optimally. The problem in this study is “Is there an increase in independence by applying the habituation method to children in IT Khadijak Al Kubro Kindergarten?”. The purpose of the study was to determine the increase in the ability of independence by applying the habituation method at Khadijah Alkubro Kindergarten Bangkinang Kota. This research method is classroom action research (PTK) which is carried out 2 cycles. This research was conducted from July 15, 2024 - July 25, 2024. The subjects in this study were children aged 5-6 years at Khadijah Al-Kubro Kindergarten, namely 15 children. Data collection in this study used observation sheets and documentation. The results of this study showed that in cycle I there was an increase to 64% and in cycle II there was an increase to 83%. Thus, it can be concluded that the use of habituation methods can improve the ability of independence in children aged 5-6 years at Khadijah Al-Kubro Kindergarten.